Design and Model Test of a Modularized Prefabricated Steel Frame Structure with Inclined Braces - Xuechun Liu; Ailin Zhang; Jing Ma; Yongqiang Tan; Yu Bai (Advances in Materials Science and Engineering)
Modularized prefabricated steel structures have become the preferred design in the industrialization of steel structures due to their advantages of fast construction speed, high degree of industrialization, low labour intensity, and more. Prefabricated steel structures have some engineering applications, but all are low-rise structures with few applications in the field of high-rise buildings. Using finite element analysis with line and solid elements, full-scale experiments were conducted to study the single-span frame, which is the core load-bearing part of a modularized prefabricated high-rise steel frame structure with inclined braces. The mechanical mechanisms, computation methods, and design formulas of truss girders were obtained by comparing the finite element and model experiments and building a theoretical and experimental basis for the compilation of design codes. The mechanical characteristics under design load, the deformation and stress state, the elastic-plastic law of development, and the yield failure mode and mechanism under horizontal ultimate load were also obtained. Based on theoretical analysis, finite element analysis, and experiments, the design method of this frame was summarized and incorporated into the design code.